Selected Works of Miguel de Unamuno, Volume 5 : The Agony of Christianity and Essays on Faith - Unamuno, Miguel de, 1864-1936 (Bollingen series ;, 2015)
Unamuno's long essay on Christianity as a state of agony is followed by nine essays including "Nicodemus the Pharisee," "Faith," and "What is Truth?"